2022
DOI: 10.1136/bmjoq-2021-001709
|View full text |Cite
|
Sign up to set email alerts
|

Improving the uptake of cervical screening in pregnant and recently postnatal women: a quality improvement project

Abstract: BackgroundIn 2018, cervical screening uptake was at its lowest level since screening began, particularly in those aged 25–35, coinciding with the peak incidence of cervical cancer and average age at first delivery.ProblemRetrospective baseline data of pregnant women found 47.3% (n=123/260) were overdue for screening by delivery, of whom 74% (n=91/123) remained overdue by 6 months postnatal.MethodsWe undertook a quality improvement project from April 2018 to April 2019 to improve cervical screening uptake in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…French hospital-based studies have found similar rates of failure to catch up during pregnancy (from 53 to 61%) [ 39 – 41 ], but our work is the first study to describe this phenomenon among a national sample of pregnant women. In the UK, Coleridge et al found that nearly half (47.3%) of a sample of 260 pregnant women were overdue for cervical screening and 74% were not caught up during either their pregnancy or the first 6 months postpartum [ 42 ]. In Brazil, Terlan and Cesar have observed that, despite prenatal visits, 21.6% pregnant women did not undergo the Pap smears they should have had [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…French hospital-based studies have found similar rates of failure to catch up during pregnancy (from 53 to 61%) [ 39 – 41 ], but our work is the first study to describe this phenomenon among a national sample of pregnant women. In the UK, Coleridge et al found that nearly half (47.3%) of a sample of 260 pregnant women were overdue for cervical screening and 74% were not caught up during either their pregnancy or the first 6 months postpartum [ 42 ]. In Brazil, Terlan and Cesar have observed that, despite prenatal visits, 21.6% pregnant women did not undergo the Pap smears they should have had [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oyegbite et al showed that a nurse contacting 120 patients overdue for CCS in a small practice in northwest England increased CCS rates versus texting, but the effort required to achieve this increase was unsustainable ( Oyegbite et al, 2021 ). Another study of 260 patients showed a 8% increase in CCS for pregnant and postpartum patients by introducing a package of CCS information, targeted education, and widening access to screening appointments ( Coleridge et al, 2022 ). Other research on CCS during the COVID-19 pandemic used different changes in workflow to improve screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Ogebyte et al showed that a nurse contacting 120 patients overdue for CCS in a small practice in northwest England increased CCS rates versus texting, but the effort required to achieve this increase was unsustainable (Ogebyte, 2021). Another study of 260 patients showed a 8% increase in CCS for pregnant and postpartum patients by introducing a package of CCS information, targeted education, and widening access to screening appointments (Coleridge, 2022). Other research on CCS during the COVID-19 pandemic used different changes in workflow to improve screening rates.…”
Section: Regular Clinic Hoursmentioning
confidence: 99%